PERBEDAAN TINGKAT PENGETAHUAN DAN SIKAP PENCEGAHAN RABIES ANTARA WISATAWAN ASING DAN WISATAWAN DOMESTIK DI KAWASAN ITDC NUSA DUA - Desak Putu Yuni Sumaryani; Putu Ayu Asri Damayanti; Ida Arimurti Sanjiwani (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Bali as tourism area is stilling endemic for rabies. Tourists should have good knowledge and preventive attitude to reduce the risk of rabies exposure. This study aimed to determine the difference in the level of knowledge and preventive attitude among foreign and domestic tourists against rabies in the ITDC Nusa Dua. This research was a quantitative study, comparative descriptive with a cross sectional design. Accidental sampling technique was used to determine 40 foreign tourists and 40 domestic tourists as a sample that was taken in the ITDC Nusa Dua. Data collection was carried out by using questionnaires to find out demographic data, level of knowledge and preventive attitude. The results showed that foreign tourist knowledge was categorized as good (72,5%), sufficient (25%) and lack (2,5%), while domestic tourist knowledge was categorized as good (70%), sufficient (25%) and lack (5%). Foreign tourist preventive attitude was categorized as good (10%), sufficient (77,5%) and lack (12,5%), while domestic tourist preventive attitude was categorized as good (5%), sufficient (95%). The results of statistical test showed that there was no difference in the level of knowledge among foreign and domestic tourists (p value = 0.942; ? = 0.05) and also there was no difference in the preventive attitudes among foreign and domestic tourists (p value = 0.422; ? = 0.05). Knowledge and preventive attitude between foreign and domestic tourists are same, majority the level of knowledge is in the good category and preventive attitude is in sufficient category. The results of this study will make it easier to provide health information among tourists to reduce rabies cases.